Tracking the performance, energetics and biomechanics of international versus national level swimmers during a competitive season - Costa, M.J. (2012)
The purpose of this study was to track and compare the changes of performance, energetic and biomechanical profiles of international (Int) and national (Nat) level swimmers during a season. Ten Portuguese male swimmers (four Int and six Nat level subjects) were evaluated on three different time periods (TP1, TP2, TP3) of the 2009–2010 season. Swimming performance was assessed based on official time’s lists of the 200-m freestyle event. An incremental set of 7 9 200 m swims was applied to assess the energetic and biomechanical data. Measurements were made of: (1) velocity at the 4 mmol of lactate levels (V4), stroke index at V4 (SI@V4) and propelling efficiency at V4 (gp@V4), as energetic estimators; (2) stroke length at V4 (SL@V4) and stroke frequency at V4 (SF@V4), as biomechanical variables. The results demonstrated no significant variations in all variables throughout the season. The inter-group comparison pointed out higher values for Int swimmers, with statistical differences for the 200 m performance in all time periods. Near values of the statistical significance were demonstrated for the SI@V4 in TP1 and TP3. The tracking based on K values was high only for the SI@V4. It is concluded that a high stability can be observed for elite swimmers performance, energetic and biomechanical profiles throughout a single season. Int swimmers are able to maintain a higher energetic and biomechanical capacity than Nat ones at all times. The SI@V4 may be used as an indicator of performance variation.